pH-sensitive supramolecular self-assembled peptide hydrogel for the treatment of esophageal cancer - Ye, Gaobing; Luo, Shiyao; Zafar, Hajra; Ge, Honglei; Liu, Binbin; Wang, Nan; Jin, Yu; Wang, Miao; Chen, Xu; Ye, Xiaoming (Frontiers in Pharmacology, 2024)
Esophageal cancer is one of the most common cancers in the world which ranks the sixth in cancer-related mortality. Doxorubicin (DOX), as a classic broad-spectrum and non-specific small molecular anti-tumor drug, has achieved widespread use including the treatment of esophageal cancer. However, due to its strong cardiotoxicity, poor tumor targeting ability and short half-time, the clinical application of DOX has been greatly limited. In this research, we designed and successfully synthesized a peptide sequenced IEIIIK (IEK for short) with excellent pH responsiveness. Under physiological conditions (pH 7.4), the peptide can encapsulate DOX and self-assemble into a stable hydrogel (DOX-IEK) through hydrophobic and electrostatic interactions.After being injected into acidic tumor microenvironment, protonation degree of alkaline amino acid lysine increased and negative charge of glutamate decreased, directly leading to enhanced electrostatic repulsion and the following hydrogel dissociation. Released DOX can accumulate at tumor tissue and achieve an anti-tumor efficacy. More importantly, the hydrogel can act as a drug reservoir for sustained drug release, improving drug targeting ability, prolonging the duration of drug administration to make up for the short half-time of DOX and reducing systemic toxicity. Ideal antitumor efficacy has been achieved both in the in vitro and in vivo experiments.